Bipolar magnetic semiconductors among intermediate states during the conversion from Sc2C(OH)2 to Sc2CO2 MXene. Issue 18 (30th April 2018) - Zha, Xian-Hu; Ren, Ji-Chang; Feng, Li; Bai, Xiaojing; Luo, Kan; Zhang, Yaqing; He, Jian; Huang, Qing; Francisco, Joseph S.; Du, Shiyu
Abstract : Bipolar magnetic semiconductors for spintronics determined in the intermediate states Sc2 C(OH) x O2− x from Sc2 C(OH)2 to Sc2 CO2 . Abstract : MXenes represent a new family of two-dimensional materials that have attracted considerable attention in recent years. Because of the remarkably different structures of Sc2 C(OH)2 and Sc2 CO2 MXene and their recently reported properties, this study explored the structural evolution and mechanism of chemical conversion between these two MXenes. Using first-principles density functional theory (DFT), the mechanism for dehydrogenation/hydrogenation is investigated by gradually removing/adding surface hydrogen atoms for Sc2 C(OH)2 /Sc2 CO2 supercells. Employing three different supercells (2 × 2 × 1, 3 × 3 × 1 and 4 × 4 × 1), intermediate states Sc2 C(OH) x O2− x with varying hydrogen content x (0.0625≤ x ≤ 1.94) are obtained. The results show that the trend is to minimize the difference in the number of hydrogen atoms and the distance between them on the two sides of the monolayer. This feature is found to be generally applicable to other functional groups of MXenes during surface conversion. Analysis of these structures shows that all the oxygen, carbon and scandium atoms remain in essentially the same locations as in Sc2 C(OH)2 until atoms rearrange in the carbon layer at sufficiently low x . Regarding the electronic properties, the behavior of the rearranged configurations is found to depend on the structure, moving beyond the conventional model of p-type doping induced by dehydrogenation. Bipolar magnetic semiconductors (BMSs) are identified from these rearranged configurations by the inhomogeneous distribution of hydrogen atoms on the different sides and x values approximately in the range of 0.188 ≤ x ≤ 0.812. Findings from this study suggest that the intrinsic spin-polarized semiconducting characteristics of Sc2 C(OH) x O2− x are expected to be experimentally observable if samples are prepared as nanoscale flakes. The current results indicate that Sc-based MXene may be a promising material for nanoscale spintronic devices.